Iron-silicon magnetic powder, iron-silicon magnetic core and preparation method and application of iron-silicon magnetic powder and iron-silicon magnetic core

By preparing layered iron-silicon magnetic powder and coating its surface with an insulating layer, the problem of low magnetic permeability of iron-silicon magnetic powder cores was solved, realizing iron-silicon magnetic cores with high magnetic permeability and low loss, which are suitable for high-power inductor devices.

CN120895353APending Publication Date: 2025-11-04HENGDIAN GRP DMEGC MAGNETICS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511010363.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-22
Publication Date
2025-11-04

AI Technical Summary

Technical Problem

The low permeability and high coercivity of existing iron-silicon magnetic powder core materials limit their application in high-power electronic components.

Method used

A high-permeability, low-coercivity iron-silicon magnetic core was prepared by using a layered iron-silicon core with a nanoscale insulating coating on its surface, forming an acid passivation film through acid infiltration, and combining ultrasonic vibration and molding processes.

Benefits of technology

The permeability of the iron-silicon magnetic powder core is improved, while the loss and coercivity are reduced, making it suitable for high-power inductor devices and improving the stability and performance of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120895353A_ABST
    Figure CN120895353A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of soft magnetic materials, and particularly relates to iron-silicon magnetic powder, an iron-silicon magnetic core and a preparation method and application of the iron-silicon magnetic powder and the iron-silicon magnetic core. The invention provides iron-silicon magnetic powder. The iron-silicon magnetic powder provided by the invention is lamellar iron-silicon magnetic powder; the iron-silicon magnetic powder comprises a lamellar iron-silicon core and an insulating coating layer coating the surface of the iron-silicon core, the iron-silicon magnetic powder reaches the iron-silicon core through the acid permeation insulating coating layer, so that the iron-silicon core is tightly attached to the interface of the insulating coating layer to form an acid passivation film. The iron-silicon magnetic powder disclosed by the invention has high magnetic conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of soft magnetic materials, and particularly relates to a ferrosilicon magnetic powder, a ferrosilicon magnetic core and a preparation method and application thereof. BACKGROUND

[0002] Soft magnetic materials play a role in energy storage, current limiting, filtering and the like in circuits, and have the dual effects of protecting circuits and transmitting energy. With the increasing complexity and energy density of circuits, the power and efficiency required by electronic components are also increasing, thereby greatly increasing the requirements for the magnetic permeability and saturation magnetic flux Bs of the soft magnetic materials used in the components. Soft magnetic materials mainly include three types: ferrite soft magnetic, amorphous nanocrystalline soft magnetic and metal magnetic powder core soft magnetic. The magnetic permeability of the latter is greatly different from that of the former two, and the application market of the latter is increasingly squeezed by the former two. The metal magnetic powder core is a soft magnetic product formed by coating a core-shell structure magnetic powder on the surface of a metal magnetic powder through powder metallurgy, and due to the large number of air gaps in the structure and the influence of the demagnetizing field of the spherical magnetic powder itself, the magnetic permeability of the metal magnetic powder core soft magnetic material is relatively low, and in particular, the magnetic permeability of the ferrosilicon magnetic powder core is only in the order of 100, which is used on a large scale. Although the ferrosilicon metal magnetic powder core has a high saturation magnetic flux Bs and a low price advantage, how to improve the energy density, increase the magnetic permeability and reduce the loss is the key to the further development of the ferrosilicon magnetic powder core material. The existing ferrosilicon magnetic powder core material has low magnetic permeability (≤90) and high coercivity, which restricts its development. SUMMARY

[0003] Therefore, the technical problem to be solved by the application is to overcome the defect of low magnetic permeability of the existing ferrosilicon magnetic core material, so as to provide a ferrosilicon magnetic powder, a ferrosilicon magnetic core and a preparation method and application thereof.

[0004] The application provides a ferrosilicon magnetic powder, which is a flaky ferrosilicon magnetic powder.

[0005] The ferrosilicon magnetic powder comprises a flaky ferrosilicon inner core and an insulating coating layer coated on the surface of the ferrosilicon inner core.

[0006] The ferrosilicon magnetic powder is subjected to acid penetration of the insulating coating layer to the ferrosilicon inner core, so that an acid passivation film is formed at the interface between the ferrosilicon inner core and the insulating coating layer.

[0007] Preferably, the ferrosilicon inner core comprises a ferrosilicon alloy.

[0008] The ferrosilicon alloy comprises, in terms of mass percentage, 93.2-96.2wt% of iron and 3.8-6.8wt% of silicon.

[0009] The insulating coating layer is coated on the surface of the ferrosilicon inner core, and the insulating coating layer comprises an insulating coating raw material. The average particle size of the nanoscale insulating coating raw material is 200-500nm.

[0010] And / or, the insulation coating material in the insulation coating layer comprises at least one of nanoscale mica powder, nanoscale silicon dioxide, nanoscale aluminum oxide, nanoscale kaolin;

[0011] And / or, the acid comprises at least one of phosphoric acid, chromic acid, phytic acid.

[0012] The present application provides a preparation method of the above-mentioned iron-silicon magnetic powder, comprising the following steps:

[0013] 1) Take the iron-silicon alloy melt to carry out gas atomization powdering to obtain alloy powder, mix the alloy powder, a surfactant and a first solvent for ball milling to obtain a ball milling material;

[0014] 2) Mix the ball milling material obtained in step 1), an insulation coating material and a dispersant, dry, then immerse the dried solid material in an acid-containing organic solvent, and obtain the iron-silicon magnetic powder after the immersion is completed.

[0015] Preferably, the surfactant in step 1) is selected from at least one of oleic acid, lauric acid, and sodium secondary alkyl sulfonate (SAS-60);

[0016] And / or, the first solvent is selected from acetone;

[0017] And / or, the mass ratio of the alloy powder, the surfactant and the first solvent is (3.5-7.0):(1-1.5):(7.5-12.5);

[0018] And / or, the mass ratio of the grinding balls used in the ball milling to the alloy powder is (3.5-7):(1-1.5);

[0019] Optionally, the grinding balls of the ball milling comprise spherical agate grinding balls;

[0020] Optionally, the diameter of the grinding balls of the ball milling is 3-8mm;

[0021] And / or, the rotation speed of the ball milling is 250-500rpm, and the ball milling time is 4-5h;

[0022] And / or, the atomization gas pressure of the gas atomization powdering is 18-22bar;

[0023] Optionally, the atomization gas of the gas atomization powdering is selected from an inert gas;

[0024] Optionally, the atomization gas of the gas atomization powdering is nitrogen.

[0025] And / or, the gas atomization step also includes a step of screening the alloy powder after gas atomization, and mixing the alloy powder with a surface active agent and a first solvent for ball milling.

[0026] Optionally, the ball milling step also includes a step of cleaning and drying after the ball milling step.

[0027] Optionally, the cleaning agent used in the cleaning step includes acetone.

[0028] Preferably, the mass ratio of the ball milling material and the insulating coating raw material in step 1) is 1:(0.001-0.012).

[0029] And / or, the mass ratio of the ball milling material and the dispersant is 1:(1-4).

[0030] And / or, the dispersant is selected from acetone.

[0031] And / or, the mass ratio of the acid in the acid-containing organic solvent to the mass of the ball milling material in the dried solid material is (0.004-0.008):1.

[0032] And / or, the organic solvent is selected from acetone.

[0033] And / or, the mass ratio of the acid in the acid-containing organic solvent to the mass of the organic solvent is 1:(2-4).

[0034] And / or, the impregnation time is 5-15 min.

[0035] The present application provides an iron-silicon magnetic core prepared from the iron-silicon magnetic powder or the iron-silicon magnetic powder prepared by the preparation method.

[0036] The present application provides a preparation method of an iron-silicon magnetic core, comprising the following steps:

[0037] Mixing the iron-silicon magnetic powder or the iron-silicon magnetic powder prepared by the preparation method with a lubricant, molding, and then heat treating in an inert atmosphere to obtain the iron-silicon magnetic core.

[0038] Preferably, the mass ratio of the iron-silicon magnetic powder and the lubricant is 1000:(1-5).

[0039] And / or, the lubricant is selected from zinc stearate.

[0040] And / or, the compression molding pressure is 900-1200 MPa;

[0041] And / or, the inert atmosphere comprises at least one of a nitrogen atmosphere, an argon atmosphere.

[0042] And / or, the heat treatment temperature is 700-760 DEG C, and the heat treatment time is 20-40 min.

[0043] And / or, the heat treatment temperature is 700-760 DEG C, and the heat treatment time is 20-40 min.

[0044] Preferably, the compression molding step further comprises ultrasonic vibration treatment before the compression molding step.

[0045] Optionally, the ultrasonic vibration treatment has an ultrasonic power of 50-100 W, and the ultrasonic vibration treatment time is 30-180 s.

[0046] Optionally, the ultrasonic vibration treatment further comprises pre-pressing treatment; the pre-pressing treatment is performed while the ultrasonic vibration is achieved, so that the iron-silicon magnetic powder can be adjusted in position under the vibration, and the iron-silicon magnetic powder can be prevented from flying up due to the vibration, so that the powder loss is reduced.

[0047] Optionally, the pre-pressing treatment has a pressure of 48-52 MPa.

[0048] The application provides an application of the above-mentioned iron-silicon magnetic powder, the above-mentioned iron-silicon magnetic powder prepared by the above-mentioned preparation method, the above-mentioned iron-silicon magnetic core or the above-mentioned iron-silicon magnetic core prepared by the above-mentioned preparation method in an inductor device.

[0049] The technical scheme of the application has the following advantages:

[0050] 1. The iron-silicon magnetic powder provided by the application is a laminar iron-silicon magnetic powder; the iron-silicon magnetic powder comprises a laminar iron-silicon core and an insulating coating layer covering the surface of the iron-silicon core; the acid penetrates the insulating coating layer to reach the iron-silicon core, so that an acid passivation film is formed at the interface between the iron-silicon core and the insulating coating layer. The laminar iron-silicon magnetic powder of the application affects the demagnetizing field of the magnetic powder, changes the air gap distribution in the magnetic core, and promotes the material to easily reach high permeability; the acid penetrates to the iron-silicon core, and a dense acid passivation layer is easily formed on the surface of the iron-silicon core through the passivation reaction; the insulating coating layer and the acid passivation layer work together to tightly cover the iron-silicon inner layer, the insulating resistance is high, and the acid passivation layer is not easy to fall off; the synergistic insulation treatment can better reduce the loss (mainly including eddy current loss). The iron-silicon magnetic powder of the application has high permeability.

[0051] 2. The iron-silicon magnetic powder provided by the application also has the advantages of reducing the coercive force and reducing the loss.

[0052] 3. The preparation method of the iron-silicon magnetic powder provided by the present application comprises the following steps: 1) taking an iron-silicon alloy melt to perform gas atomization powdering to obtain alloy powder, mixing the alloy powder, a surfactant and a first solvent to perform ball milling to obtain a ball milling material; 2) mixing the ball milling material obtained in step 1), a nanoscale insulation coating raw material and a dispersant, drying, and then immersing the dried solid material in an acid-containing organic solvent to obtain the iron-silicon magnetic powder. In the present application, the alloy powder is formed after the iron-silicon binary alloy melt, the surfactant is added and the ball milling external force is used to change the structure of the magnetic powder, the sheet-shaped metal soft magnetic material is formed, then the nanoscale insulation coating raw material is adsorbed on the surface of the sheet-shaped metal soft magnetic material to form an iron-silicon core surface insulation coating layer structure, and then the acid-containing organic solvent is used for immersion, the acid penetrates the insulation coating layer to reach the iron-silicon core, the passivation reaction occurs on the surface of the iron-silicon core to easily form a dense acid passivation layer, and the iron-silicon magnetic powder with the specific structure of the present application is obtained. The iron-silicon magnetic powder obtained by the preparation method of the present application has high magnetic permeability.

[0053] 3. The preparation method of the iron-silicon magnetic powder provided by the present application has simple preparation process, convenient operation, high production efficiency, and the obtained high iron-silicon magnetic powder product has few micro defects, low coercive force and low loss.

[0054] 4. The preparation method of the iron-silicon magnetic core provided by the present application comprises the following steps: mixing the iron-silicon magnetic powder of claim 1 or 2 or the iron-silicon magnetic powder prepared by the preparation method of any one of claims 3-5 with a lubricant, performing die molding, and then performing heat treatment in an inert atmosphere to obtain the iron-silicon magnetic core. The preparation method of the iron-silicon magnetic core of the present application is simple, and different properties such as ring shape, rod shape, linear shape and the like can be obtained by die molding according to actual needs, and the obtained iron-silicon magnetic core has high magnetic permeability.

[0055] 5. The preparation method of the iron-silicon magnetic core provided by the present application further comprises an ultrasonic vibration treatment before the die molding step; the iron-silicon magnetic powder is driven in an ultrasonic vibration mode before pressing to adjust the arrangement, the iron-silicon magnetic powder tends to be parallel arrangement, the horizontal or vertical arrangement of the iron-silicon magnetic powder is reduced, the extrusion of the magnetic powder and the magnetic powder edges in the pressing process is reduced, the excessive crushing or pulverization during die molding is avoided to affect the internal structure of the iron-silicon magnetic core, the air gap distribution between the powders is further improved, and the sheet-shaped iron-silicon magnetic powder is arranged in a maximum area laminated contact, which can further promote the rapid magnetization of the iron-silicon magnetic core and further improve the magnetic permeability of the iron-silicon magnetic core.

[0056] 6. The preparation method of the iron-silicon magnetic core provided by the present application has the advantages of low coercive force and low loss. BRIEF DESCRIPTION OF DRAWINGS

[0057] In order to more clearly illustrate the technical solutions in the specific embodiments of the present application or the prior art, the following will briefly introduce the drawings needed to be used in the specific embodiments or the prior art description. Obviously, the drawings described below are some embodiments of the present application, and for those skilled in the art, other drawings can also be obtained without creative labor based on these drawings.

[0058] Figure 1 The fracture morphology of the iron-silicon magnetic core prepared in Example 1 of the present application;

[0059] Figure 2 The fracture morphology of the iron-silicon magnetic core prepared in Example 1 of the present application;

[0060] Figure 3 The fracture morphology of the iron-silicon magnetic core prepared in Example 1 of the present application; DETAILED DESCRIPTION

[0061] The following examples are provided to better further understand the present application, and are not limited to the best mode, and do not constitute a limitation on the content and scope of protection of the present application. Any person under the inspiration of the present application or the combination of the present application with other prior art features can obtain any product same or similar to the present application, which falls within the scope of protection of the present application.

[0062] If the specific experimental steps or conditions are not indicated in the examples, the operation or conditions can be carried out according to the conventional experimental steps described in the literature in the art. If the reagents or instruments are not indicated by the manufacturer, they are conventional reagent products that can be obtained by market purchase.

[0063] Example 1

[0064] The present embodiment provides a preparation method of iron-silicon magnetic powder, comprising the following steps:

[0065] 1) Take iron-silicon alloy (iron 95.2wt%, silicon 4.8wt%) vacuum melting to carry out gas atomization powdering to obtain alloy powder, the atomizing gas for gas atomization powdering is nitrogen, the atomizing gas pressure is 20bar, and the alloy powder is sieved into 200-500 mesh particle size range, 200g of 200-500 mesh particle size range alloy powder, 40g of oleic acid and 400g of acetone are mixed and loaded into a ball mill tank at 400rpm for 4h, the grinding balls are multiple spherical agates with different diameters of 3-8mm, the total weight of the grinding balls is 1000g, then the powder is taken out, washed with acetone and dried to obtain a ball mill material;

[0066] 2) The ball milling material obtained in step 1) and nano-sized mica powder (average particle size of 400 nm) are mixed in acetone dispersant at a mass ratio of 1:0.008, and the mass ratio of ball milling material to dispersant is 1:2. After stirring and mixing for 15 min, the mixture is dried to form an insulating coating of nano-sized mica powder on the surface of the ball milling material. Then, the dried solid material is immersed in acetone phosphate solution for 13 min. The acetone phosphate solution penetrates into the surface of the ball milling material and reacts chemically with the alloy to form a phosphoric acid passivation film. After immersion, the iron-silicon magnetic powder is obtained. The mass ratio of phosphoric acid in the acetone phosphate solution to the mass of ball milling material in the dried solid material is 0.006:1, and the mass ratio of phosphoric acid to acetone is 1:3.

[0067] The iron-silicon magnetic powder prepared in this embodiment is a layered iron-silicon magnetic powder (e.g. Figure 1 As shown, secondary electron (SE) scanning imaging was used; the iron-silicon magnetic powder includes a lamellar iron-silicon core (95.2 wt% iron, 4.8 wt% silicon) and an insulating coating layer covering the surface of the iron-silicon core; an acid passivation film is formed at the interface between the iron-silicon core and the insulating coating layer of the iron-silicon magnetic powder.

[0068] This embodiment also provides a method for preparing an iron-silicon magnetic core, comprising the following steps:

[0069] 1 kg of the prepared iron-silicon magnetic powder and 4 g of zinc stearate were mixed evenly in a mixing tank, then transferred to a mold cavity of a press. An ultrasonic vibrator was applied to the mold at 70 W for 50 seconds, while the pressure on the mold was gradually increased to 50 MPa. After ultrasonication, the mold was quickly pressed into a ring (26.9 mm OD × 14.7 mm ID × 8.2 mm Ht) at 1000 MPa. The ring was then placed in a nitrogen atmosphere and heat-treated at 730 °C for 30 minutes, with the heating process not exceeding 120 minutes, to obtain the iron-silicon magnetic core. The fracture surface of the obtained iron-silicon magnetic core was imaged using secondary electron (SE) scanning, and the results are as follows: Figure 2 As shown.

[0070] Example 2

[0071] This embodiment provides a method for preparing iron-silicon magnetic powder, including the following steps:

[0072] 1) Take the iron-silicon alloy (iron 94.5wt%, silicon 5.5wt%) vacuum melting to carry out gas atomization powder to obtain alloy powder, the atomizing gas for gas atomization powder is nitrogen, the atomizing gas pressure is 20 bar, and the alloy powder is sieved into the 200-500 mesh particle size range, 200g of the 200-500 mesh particle size range alloy powder, 40g of oleic acid and 400g of acetone are mixed and loaded into a ball mill tank to mill at 400rpm for 5h, the grinding balls are multiple spherical agates with diameters of 3-8mm, and the total weight of the grinding balls is 1000g, then the powder is taken out, washed with acetone and dried to obtain the ball mill material;

[0073] 2) The ball mill material obtained in step 1) and nano-sized mica powder (average particle size 400nm) are mixed in an acetone dispersant at a mass ratio of 1:0.008, the mass ratio of the ball mill material and the dispersant is 1:2, and after stirring and mixing for 15min, the mixture is dried to realize the coating of the nano-sized mica powder insulation coating layer on the surface of the ball mill material, then the dried solid material is immersed in a phosphoric acid acetone solution for 13min; after the phosphoric acid acetone solution penetrates to the surface of the ball mill material and reacts with the alloy to form a phosphoric acid passivation film, the iron-silicon magnetic powder is obtained. The mass ratio of phosphoric acid in the phosphoric acid acetone solution to the mass of the ball mill material in the dried solid material is 0.006:1, and the mass ratio of phosphoric acid to acetone is 1:3.

[0074] The iron-silicon magnetic powder prepared in this embodiment is a flaky iron-silicon magnetic powder; the iron-silicon magnetic powder comprises a flaky iron-silicon core (iron 94.5wt%, silicon 5.5wt%) and an insulation coating layer coated on the surface of the iron-silicon core; the iron-silicon core of the iron-silicon magnetic powder forms an acid passivation film at the interface close to the insulation coating layer.

[0075] This embodiment also provides a preparation method of an iron-silicon magnetic core, comprising the following steps:

[0076] 1kg of the above prepared iron-silicon magnetic powder and 4g of zinc stearate are uniformly placed in a mixing tank, then transferred into a mold cavity of a press machine, an ultrasonic vibration machine is loaded on the mold, oscillated at 70w power for 50 seconds, and at the same time, the mold is gradually pressed to 50MPa, after the ultrasonic vibration ends, the magnetic ring is quickly pressed to 1000MPa pressure to form a ring (26.9mm OD×14.7mm ID×8.2mm Ht), then the magnetic ring is placed in a nitrogen atmosphere, heated to 730℃ for heat treatment for 30 minutes, and the heating process does not exceed 120 minutes, to obtain the iron-silicon magnetic core.

[0077] Example 3

[0078] This embodiment provides a preparation method of an iron-silicon magnetic powder, comprising the following steps:

[0079] 1) Take the iron-silicon alloy (iron 95.2wt%, silicon 4.8wt%) vacuum melting to carry out gas atomization powder to obtain alloy powder, the atomizing gas for gas atomization powder is nitrogen, the atomizing gas pressure is 20 bar, and the alloy powder is sieved into the 200-500 mesh particle size range. 200g of 200-500 mesh particle size range alloy powder, 40g of oleic acid and 400g of acetone are mixed and loaded into a ball mill tank to mill at 400rpm for 4h, the grinding balls are multiple spherical agates with diameters of 3-8mm, and the total weight of the grinding balls is 1000g. Then the powder is taken out, washed with acetone and dried to obtain the ball mill material;

[0080] 2) The ball mill material obtained in step 1) and nano-sized mica powder (average particle size 400nm) are mixed in an acetone dispersant at a mass ratio of 1:0.008, and the mass ratio of the ball mill material and the dispersant is 1:2. After stirring and mixing for 15min, the mixture is dried to realize the coating of the nano-sized mica powder insulation coating layer on the surface of the ball mill material. Then the dried solid material is immersed in a phosphoric acid acetone solution for 13min. After the phosphoric acid acetone solution penetrates to the surface of the ball mill material and reacts with the alloy to form a phosphoric acid passivation film, the iron-silicon magnetic powder is obtained. The mass ratio of phosphoric acid in the phosphoric acid acetone solution to the mass of the ball mill material in the dried solid material is 0.006:1, and the mass ratio of phosphoric acid to acetone is 1:3.

[0081] The iron-silicon magnetic powder prepared in this example is a flaky iron-silicon magnetic powder; the iron-silicon magnetic powder comprises a flaky iron-silicon core (iron 95.2wt%, silicon 4.8wt%) and an insulation coating layer coated on the surface of the iron-silicon core; and the iron-silicon core of the iron-silicon magnetic powder forms an acid passivation film at the interface close to the insulation coating layer.

[0082] This example also provides a preparation method of an iron-silicon magnetic core, comprising the following steps:

[0083] 1kg of the above prepared iron-silicon magnetic powder and 4g of zinc stearate are uniformly placed in a mixing tank, then transferred into a mold cavity of a press machine, and an ultrasonic vibration machine is loaded on the mold to oscillate at 70w power for 50 seconds, while gradually applying pressure to 50MPa on the mold. After ultrasonic vibration, the magnetic ring is quickly pressed at a pressure of 1200MPa to form a ring (26.9mm ODx14.7mm IDx8.2mm Ht). Then the magnetic ring is placed in a nitrogen atmosphere and heated to 730℃ for heat treatment for 30min, and the heating process does not exceed 120min. The iron-silicon magnetic core is obtained.

[0084] Example 4

[0085] This example provides a preparation method of an iron-silicon magnetic powder, comprising the following steps:

[0086] 1) Take the iron-silicon alloy (iron 94.5wt%, silicon 5.5wt%) vacuum melting to carry out gas atomization powder to obtain alloy powder, the atomizing gas for gas atomization powder is nitrogen, the atomizing gas pressure is 20 bar, and the alloy powder is sieved into the 200-500 mesh particle size range, 200g of the 200-500 mesh particle size range alloy powder, 40g of oleic acid and 400g of acetone are mixed and loaded into a ball mill tank to mill at 400rpm for 5h, the grinding balls are multiple spherical agates with diameters of 3-8mm, and the total weight of the grinding balls is 1000g, then the powder is taken out, washed with acetone and dried to obtain the ball mill material;

[0087] 2) The ball mill material obtained in step 1) and nano-sized mica powder (average particle size 400nm) are mixed in an acetone dispersant at a mass ratio of 1:0.008, the mass ratio of the ball mill material and the dispersant is 1:2, and after stirring and mixing for 15min, the mixture is dried to realize the coating of the nano-sized mica powder insulation coating layer on the surface of the ball mill material, then the dried solid material is immersed in a phosphoric acid acetone solution for 13min; after the phosphoric acid acetone solution penetrates to the surface of the ball mill material and reacts with the alloy to form a phosphoric acid passivation film, the iron-silicon magnetic powder is obtained. The mass ratio of phosphoric acid in the phosphoric acid acetone solution to the mass of the ball mill material in the dried solid material is 0.006:1, and the mass ratio of phosphoric acid to acetone is 1:3.

[0088] The iron-silicon magnetic powder prepared in this embodiment is a flaky iron-silicon magnetic powder; the iron-silicon magnetic powder comprises a flaky iron-silicon core (iron 94.5wt%, silicon 5.5wt%) and an insulation coating layer coated on the surface of the iron-silicon core; the iron-silicon core of the iron-silicon magnetic powder forms an acid passivation film at the interface close to the insulation coating layer.

[0089] This embodiment also provides a preparation method of an iron-silicon magnetic core, comprising the following steps:

[0090] 1kg of the above prepared iron-silicon magnetic powder and 4g of zinc stearate are uniformly placed in a mixing tank, then transferred into a mold cavity of a press machine, an ultrasonic vibration machine is loaded on the mold to oscillate at a power of 70w for 50 seconds, while gradually applying a pressure of 50MPa to the mold, after the ultrasonic vibration ends, the magnetic ring is quickly pressed at a pressure of 1200MPa to form a ring (26.9mm OD×14.7mm ID×8.2mm Ht), then the magnetic ring is placed in a nitrogen atmosphere, heated to 730℃ and heat treated for 30min, the heating process does not exceed 120min, and the iron-silicon magnetic core is obtained.

[0091] Example 5

[0092] This embodiment provides a preparation method of an iron-silicon magnetic powder, comprising the following steps:

[0093] 1) Take the iron-silicon alloy (iron 95.2wt%, silicon 4.8wt%) vacuum melting to carry out gas atomization powdering to obtain alloy powder, the atomizing gas for gas atomization powdering is nitrogen, the atomizing gas pressure is 20 bar, and the alloy powder is sieved into the 200-500 mesh particle size range. 200g of the 200-500 mesh particle size range alloy powder, 40g of oleic acid and 400g of acetone are mixed and loaded into a ball mill tank to mill at 250rpm for 4h, the grinding balls are multiple spherical agates with diameters of 3-8mm, and the total weight of the grinding balls is 1000g. Then, the powder is taken out, washed with acetone and dried to obtain the ball mill material;

[0094] 2) The ball mill material obtained in step 1) and nano-sized mica powder (average particle size 400nm) are mixed in an acetone dispersant at a mass ratio of 1:0.008, the mass ratio of the ball mill material and the dispersant is 1:2, and after stirring and mixing for 15min, the mixture is dried to realize the coating of the nano-sized mica powder insulation coating layer on the surface of the ball mill material. Then, the dried solid material is immersed in a phosphoric acid acetone solution for 13min. After the phosphoric acid in the phosphoric acid acetone solution penetrates to the surface of the ball mill material and reacts with the alloy to form a phosphoric acid passivation film, the iron-silicon magnetic powder is obtained. The mass ratio of phosphoric acid in the phosphoric acid acetone solution to the mass of the ball mill material in the dried solid material is 0.006:1, and the mass ratio of phosphoric acid to acetone is 1:3.

[0095] The iron-silicon magnetic powder prepared in this embodiment is a flaky iron-silicon magnetic powder; the iron-silicon magnetic powder comprises a flaky iron-silicon core (iron 95.2wt%, silicon 4.8wt%) and an insulation coating layer coated on the surface of the iron-silicon core; and the iron-silicon core of the iron-silicon magnetic powder forms an acid passivation film at the interface close to the insulation coating layer.

[0096] This embodiment also provides a preparation method of an iron-silicon magnetic core, comprising the following steps:

[0097] 1kg of the above-prepared iron-silicon magnetic powder and 4g of zinc stearate are uniformly placed in a mixing tank, then transferred into a mold cavity of a press mold, and an ultrasonic vibration machine is loaded on the mold to perform oscillation at a power of 70w for 50s, while gradually applying a pressure of 50MPa to the mold. After the ultrasonic vibration ends, the magnetic ring is rapidly pressed into a ring (26.9mm OD×14.7mm ID×8.2mm Ht) at a pressure of 1000MPa. Then, the magnetic ring is placed in a nitrogen atmosphere, heated to 730℃ and heat-treated for 30min, and the heating process does not exceed 120min. Thus, the iron-silicon magnetic core is obtained.

[0098] Example 6

[0099] This embodiment provides a preparation method of an iron-silicon magnetic powder, comprising the following steps:

[0100] 1) Take the iron-silicon alloy (iron 95.2wt%, silicon 4.8wt%) vacuum melting to carry out gas atomization powder to obtain alloy powder, the atomizing gas for gas atomization powder is nitrogen, the atomizing gas pressure is 20 bar, and the alloy powder is sieved into the 200-500 mesh particle size range, 200g of the 200-500 mesh particle size range alloy powder, 40g of oleic acid and 400g of acetone are mixed and loaded into a ball mill tank to mill at 500 rpm for 4h, the grinding balls are multiple spherical agates with diameters of 3-8mm, and the total weight of the grinding balls is 1000g, then the powder is taken out, washed with acetone and dried to obtain a ball mill material;

[0101] 2) The ball mill material obtained in step 1) and nano-sized mica powder (average particle size 400nm) are mixed in an acetone dispersant at a mass ratio of 1:0.008, the mass ratio of the ball mill material and the dispersant is 1:2, and after stirring and mixing for 15min, the mixture is dried to realize the coating of the nano-sized mica powder insulation coating layer on the surface of the ball mill material, then the dried solid material is immersed in a phosphoric acid acetone solution for 13min; after the phosphoric acid acetone solution penetrates to the surface of the ball mill material and reacts with the alloy to form a phosphoric acid passivation film, the iron-silicon magnetic powder is obtained. The mass ratio of phosphoric acid in the phosphoric acid acetone solution to the mass of the ball mill material in the dried solid material is 0.006:1, and the mass ratio of phosphoric acid to acetone is 1:3.

[0102] The iron-silicon magnetic powder prepared in this embodiment is a flaky iron-silicon magnetic powder; the iron-silicon magnetic powder comprises a flaky iron-silicon core (iron 95.2wt%, silicon 4.8wt%) and an insulation coating layer coated on the surface of the iron-silicon core; the iron-silicon core of the iron-silicon magnetic powder forms an acid passivation film at the interface close to the insulation coating layer.

[0103] This embodiment also provides a preparation method of an iron-silicon magnetic core, comprising the following steps:

[0104] 1kg of the above prepared iron-silicon magnetic powder and 4g of zinc stearate are uniformly placed in a mixing tank, then transferred into a mold cavity of a press mold, an ultrasonic vibration machine is loaded on the mold to oscillate at a power of 70w for 50 seconds, while gradually applying a pressure of 50MPa to the mold, after the ultrasonic vibration ends, the magnetic ring is quickly pressed at a pressure of 1000MPa to form a ring (26.9mm OD×14.7mm ID×8.2mm Ht), then the magnetic ring is placed in a nitrogen atmosphere, heated to 730℃ and heat treated for 30 minutes, the heating process does not exceed 120 minutes, and the iron-silicon magnetic core is obtained.

[0105] Example 7

[0106] This embodiment provides a preparation method of an iron-silicon magnetic powder, comprising the following steps:

[0107] 1) Take the iron-silicon alloy (iron 95.2wt%, silicon 4.8wt%) vacuum melting to carry out gas atomization powder to obtain alloy powder, the atomizing gas for gas atomization powder is nitrogen, the atomizing gas pressure is 20 bar, and the alloy powder is sieved into the 200-500 mesh particle size range, 200g of 200-500 mesh particle size range alloy powder, 40g of oleic acid and 400g of acetone are mixed and loaded into a ball mill tank to mill at 400 rpm for 4h, the grinding balls are multiple spherical agates with diameters of 3-8mm, and the total weight of the grinding balls is 1000g. Then, the powder is taken out, washed with acetone and dried to obtain a ball mill material;

[0108] 2) The ball mill material obtained in step 1) and nano-sized mica powder (average particle size 400nm) are mixed in an acetone dispersant at a mass ratio of 1:0.008, the mass ratio of the ball mill material and the dispersant is 1:2, and after stirring and mixing for 15min, the mixture is dried to realize the coating of the nano-sized mica powder insulation coating layer on the surface of the ball mill material. Then, the dried solid material is immersed in a phosphoric acid acetone solution for 13min. After the phosphoric acid in the phosphoric acid acetone solution penetrates to the surface of the ball mill material and reacts with the alloy to form a phosphoric acid passivation film, the iron-silicon magnetic powder is obtained. The mass ratio of phosphoric acid in the phosphoric acid acetone solution to the mass of the ball mill material in the dried solid material is 0.006:1, and the mass ratio of phosphoric acid to acetone is 1:3.

[0109] The iron-silicon magnetic powder prepared in this example is a flaky iron-silicon magnetic powder; the iron-silicon magnetic powder comprises a flaky iron-silicon core (iron 95.2wt%, silicon 4.8wt%) and an insulation coating layer coated on the surface of the iron-silicon core; and the iron-silicon core of the iron-silicon magnetic powder forms an acid passivation film at the interface close to the insulation coating layer.

[0110] This example also provides a preparation method of an iron-silicon magnetic core, comprising the following steps:

[0111] 1kg of the above prepared iron-silicon magnetic powder and 4g of zinc stearate are uniformly placed in a mixing tank, and then transferred into a mold cavity of a press mold, gradually pressed on the mold to 50MPa for a total of 50 seconds, and then quickly pressed into a ring (26.9mm OD x 14.7mm ID x 8.2mm Ht) at a pressure of 1000MPa. Then, the magnetic ring is placed in a nitrogen atmosphere, heated to 730℃ for heat treatment for 30 minutes, and the heating process does not exceed 120 minutes, to obtain the iron-silicon magnetic core.

[0112] Example 8

[0113] This example provides a preparation method of an iron-silicon magnetic powder, comprising the following steps:

[0114] 1) Take the iron-silicon alloy (iron 95.2wt%, silicon 4.8wt%) vacuum melting to carry out gas atomization powdering to obtain alloy powder, the atomizing gas for gas atomization powdering is nitrogen, the atomizing gas pressure is 18 bar, and the alloy powder is sieved into the 200-500 mesh particle size range. 200 g of the 200-500 mesh particle size range alloy powder, 50 g of oleic acid and 400 g of acetone are mixed and loaded into a ball mill tank to mill at 400 rpm for 4.5 h, the grinding balls are multiple spherical agates with diameters of 3-8 mm, and the total weight of the grinding balls is 1400 g. Then, the powder is taken out, washed with acetone and dried to obtain a ball mill material;

[0115] 2) The ball mill material obtained in step 1) and nano-sized mica powder (average particle size of 500 nm) are mixed in an acetone dispersant at a mass ratio of 1:0.006, and the mass ratio of the ball mill material and the dispersant is 1:3. After stirring and mixing for 15 min, the mixture is dried to realize the coating of the nano-sized mica powder insulation coating layer on the surface of the ball mill material. Then, the dried solid material is immersed in a phosphoric acid acetone solution for 5 min. After the phosphoric acid acetone solution penetrates to the surface of the ball mill material and reacts with the alloy to form a phosphoric acid passivation film, the iron-silicon magnetic powder is obtained. The mass ratio of phosphoric acid in the phosphoric acid acetone solution to the mass of the ball mill material in the dried solid material is 0.008:1, and the mass ratio of phosphoric acid to acetone is 1:2.

[0116] The iron-silicon magnetic powder prepared in this example is a flaky iron-silicon magnetic powder. The iron-silicon magnetic powder includes a flaky iron-silicon core (iron 95.2wt%, silicon 4.8wt%) and an insulation coating layer coated on the surface of the iron-silicon core. The iron-silicon core of the iron-silicon magnetic powder forms an acid passivation film at the interface close to the insulation coating layer.

[0117] This example also provides a preparation method of an iron-silicon magnetic core, which includes the following steps:

[0118] 1 kg of the iron-silicon magnetic powder prepared above is uniformly mixed with 3 g of zinc stearate in a mixing tank, and then transferred into a mold cavity of a press machine, and an ultrasonic vibration machine is loaded on the mold to oscillate at a power of 80 w for 180 s, while gradually applying a pressure of 48 MPa to the mold. After the ultrasonic vibration ends, the magnetic ring is quickly pressed into a ring (26.9 mm OD x 14.7 mm ID x 8.2 mm Ht) at a pressure of 900 MPa. Then, the magnetic ring is placed in a nitrogen atmosphere and heat treated at a temperature of 700℃ for 40 min, and the heating process does not exceed 110 min. The iron-silicon magnetic core is obtained.

[0119] Example 9

[0120] This example provides a preparation method of an iron-silicon magnetic powder, which includes the following steps:

[0121] 1) Take the iron-silicon alloy (iron 95.2wt%, silicon 4.8wt%) vacuum melting to carry out gas atomization powder to obtain alloy powder, the atomizing gas for gas atomization powder is nitrogen, the atomizing gas pressure is 22bar, and the alloy powder is screened into the 200-500 mesh particle size range. 200g of 200-500 mesh particle size range alloy powder, 40g of oleic acid and 450g of acetone are mixed and loaded into a ball mill tank to mill at 400rpm for 4h, the grinding balls are multiple spherical agates with diameters of 3-8mm, and the total weight of the grinding balls is 1000g. Then the powder is taken out, washed with acetone and dried to obtain the ball mill material;

[0122] 2) The ball mill material obtained in step 1) and nano-sized mica powder (average particle size 200nm) are mixed in an acetone dispersant at a mass ratio of 1:0.0012, and the mass ratio of the ball mill material and the dispersant is 1:4. After stirring and mixing for 15min, the mixture is dried to realize the coating of the nano-sized mica powder insulation coating layer on the surface of the ball mill material. Then the dried solid material is immersed in a phosphoric acid acetone solution for 15min. After the phosphoric acid acetone solution penetrates to the surface of the ball mill material and reacts with the alloy to form a phosphoric acid passivation film, the iron-silicon magnetic powder is obtained. The mass ratio of phosphoric acid in the phosphoric acid acetone solution to the mass of the ball mill material in the dried solid material is 0.004:1, and the mass ratio of phosphoric acid to acetone is 1:4.

[0123] The iron-silicon magnetic powder prepared in this example is a flaky iron-silicon magnetic powder; the iron-silicon magnetic powder comprises a flaky iron-silicon core (iron 95.2wt%, silicon 4.8wt%) and an insulation coating layer coated on the surface of the iron-silicon core; and the iron-silicon core of the iron-silicon magnetic powder forms an acid passivation film at the interface close to the insulation coating layer.

[0124] This example also provides a preparation method of an iron-silicon magnetic core, comprising the following steps:

[0125] 1kg of the above prepared iron-silicon magnetic powder and 5g of zinc stearate are uniformly placed in a mixing tank, then transferred into a mold cavity of a press machine, and an ultrasonic vibration machine is loaded on the mold to oscillate at a power of 100w for 30s, while gradually applying a pressure of 52MPa to the mold. After ultrasonic vibration, the magnetic ring is quickly pressed at a pressure of 1200MPa to form a ring (26.9mm ODx14.7mm IDx8.2mm Ht). Then the magnetic ring is placed in a nitrogen atmosphere and heated to 760℃ for heat treatment for 20min, and the heating process does not exceed 100min. The iron-silicon magnetic core is obtained.

[0126] Comparative Example 1

[0127] This comparative example provides a preparation method of an iron-silicon magnetic powder, comprising the following steps:

[0128] 1) Take an iron-silicon alloy (95.2wt% iron, 4.8wt% silicon) and melt it under vacuum. Then, perform gas atomization to obtain alloy powder. The atomizing gas for gas atomization is nitrogen, and the atomizing gas pressure is 20 bar. The alloy powder is sieved into a particle size range of 200-500 mesh. Mix 200g of alloy powder in the 200-500 mesh particle size range with 400g of acetone and put it into a ball mill jar. Ball mill at 400rpm for 4h. The grinding balls are multiple spherical agate balls with a diameter of 3-8mm. The total weight of the grinding balls is 1000g. Then, take out the powder, wash it with acetone, and dry it to obtain the ball milling material.

[0129] 2) The ball milling material obtained in step 1) and nano-sized mica powder (average particle size of 400 nm) are mixed in acetone dispersant at a mass ratio of 1:0.008, and the mass ratio of ball milling material to dispersant is 1:2. After stirring and mixing for 15 min, the mixture is dried to form an insulating coating of nano-sized mica powder on the surface of the ball milling material. Then, the dried solid material is immersed in acetone phosphate solution for 13 min. The acetone phosphate solution penetrates into the surface of the ball milling material and reacts chemically with the alloy to form a phosphoric acid passivation film. After immersion, the iron-silicon magnetic powder is obtained. The mass ratio of phosphoric acid in the acetone phosphate solution to the mass of ball milling material in the dried solid material is 0.006:1, and the mass ratio of phosphoric acid to acetone is 1:3.

[0130] The iron-silicon magnetic powder prepared in this comparative example is spherical or large-particle iron-silicon magnetic powder (e.g. Figure 3 As shown, using secondary electron (SE) scanning imaging, it differs greatly from the layered structure in Example 1; the iron-silicon magnetic powder includes an iron-silicon core (95.2 wt% iron, 4.8 wt% silicon) and an insulating coating layer covering the surface of the iron-silicon core; an acid passivation film is formed at the interface between the iron-silicon core and the insulating coating layer of the iron-silicon magnetic powder.

[0131] This comparative example also provides a method for preparing an iron-silicon magnetic core, comprising the following steps:

[0132] 1 kg of the iron-silicon magnetic powder prepared above and 4 g of zinc stearate were placed in a mixing tank and mixed evenly. Then, the mixture was transferred to the mold cavity of a press. An ultrasonic vibrator was applied to the mold and vibrated at 70 W for 50 seconds. At the same time, the pressure on the mold was gradually increased to 50 MPa. After the ultrasonic treatment, the mold was quickly pressed into a ring (26.9 mm OD × 14.7 mm ID × 8.2 mm Ht) at a pressure of 1000 MPa. The magnetic ring was then placed in a nitrogen atmosphere and heat-treated at 730 °C for 30 minutes. The heating process did not exceed 120 minutes to obtain the iron-silicon magnetic core.

[0133] Comparative Example 2

[0134] This comparative example provides a method for preparing iron-silicon magnetic powder, comprising the following steps:

[0135] 1) Take the iron-silicon alloy (iron 95.2wt%, silicon 4.8wt%) vacuum melting for gas atomization powder to obtain alloy powder, the atomizing gas for gas atomization powder is nitrogen, the atomizing gas pressure is 20 bar, and the alloy powder is sieved into the particle size range of 200-500 meshes. 200 g of 200-500 mesh size range alloy powder, 40 g of oleic acid and 400 g of acetone are stirred and mixed for 4 h, and then the powder is taken out and washed with acetone and dried to obtain the treated material;

[0136] 2) The treated material obtained in step 1) and nano-sized mica powder (average particle size 400 nm) are mixed in a dispersant at a mass ratio of 1:0.008, the mass ratio of the treated material and the dispersant is 1:2, and after stirring and mixing for 15 min, the treated material is dried to realize the surface coating of the nano-sized mica powder insulation coating layer, and then the dried solid material is immersed in a phosphoric acid acetone solution for 13 min; after the phosphoric acid acetone solution penetrates to the surface of the treated material and reacts with the alloy to form a phosphoric acid passivation film, the iron-silicon magnetic powder is obtained. The mass ratio of phosphoric acid in the phosphoric acid acetone solution to the mass of the treated material in the dried solid material is 0.006:1, and the mass ratio of phosphoric acid to acetone is 1:3.

[0137] The iron-silicon magnetic powder prepared in the present comparative example is a spherical iron-silicon magnetic powder; the iron-silicon magnetic powder comprises an iron-silicon core (iron 95.2wt%, silicon 4.8wt%) and an insulation coating layer coated on the surface of the iron-silicon core; the interface between the iron-silicon core of the iron-silicon magnetic powder and the insulation coating layer forms an acid passivation film.

[0138] The present comparative example also provides a preparation method of an iron-silicon magnetic core, comprising the following steps:

[0139] 1 kg of the above prepared iron-silicon magnetic powder and 4 g of zinc stearate are uniformly placed in a mixing tank, then transferred into a mold cavity of a press machine, an ultrasonic vibration machine is loaded on the mold, oscillated at a power of 70 w for 50 seconds, and at the same time, the mold is gradually pressed to 50 MPa. After ultrasonic vibration, the magnetic ring is quickly pressed to 1000 MPa pressure to form a ring (26.9 mm OD x 14.7 mm ID x 8.2 mm Ht), and then the magnetic ring is placed in a nitrogen atmosphere and heated to 730°C for heat treatment for 30 minutes, and the heating process does not exceed 120 minutes, to obtain the iron-silicon magnetic core.

[0140] Test Example

[0141] The density of the iron-silicon magnetic cores prepared in Examples 1-7 and Comparative Examples 1-2 was tested by using Archimedes drainage method, and the density test results are shown in Table 1. Then, the iron-silicon magnetic cores prepared in Examples 1-7 and Comparative Examples 1-2 were wound with enameled copper wire to pass through the inner hole of the iron-silicon magnetic core uniformly and tightly and to be wound, with 20 turns of primary coil and 20 turns of secondary coil, to obtain magnetic ring test samples. The inductance of the above magnetic ring test samples at 100 kHz was tested by using an inductance meter LCR CH3303, and then the permeability was converted, and the permeability test results are shown in Table 1. The conversion formula of permeability is as follows:

[0142] Wherein: μ i : permeability of the iron-silicon magnetic core; L: inductance (unit: H); N: number of turns of coil; l e : effective magnetic path length (unit: cm, average circumference of the annular iron-silicon magnetic core); A e : effective cross-sectional area (unit: cm 2 , cross-sectional area of the iron-silicon magnetic core). The saturation magnetic flux Bs of the above magnetic ring test samples was measured by using an alternating B-H meter, with a magnetic field frequency of 50 Hz and a magnetic field strength of 50000 A / m, and the saturation magnetic flux test results are shown in Table 1.

[0143] Table 1

[0144]

[0145]

[0146] By comparison, the permeability of each magnetic ring in Examples 1-6 is greater than 150, which can indicate that the flaky magnetic powder formed by changing the shape of the iron-silicon magnetic powder by external force, and then subjected to secondary strengthening insulation coating and ultrasonic vibration orientation before pressing, can greatly improve the permeability of the magnetic ring. Compared with the existing spherical magnetic powder core material, the improvement is even more than 100%, which fully demonstrates the advantages of the present application. In Example 7, the magnetic core is not subjected to ultrasonic vibration orientation during preparation, and the permeability is lower than that of other examples.

[0147] By changing the shape of the magnetic powder and manufacturing flaky magnetic powder with easy magnetization, the magnetic powder is subjected to ultrasonic vibration orientation before pressing, and the powder tends to be parallel arrangement, which reduces the extrusion of the magnetic powder and the corners of the magnetic powder during pressing, improves the air gap distribution between the powders, changes the demagnetizing field of the magnetic powder and the air gap compression, and greatly improves the permeability of the material.

[0148] Obviously, the above embodiments are merely example for clearly illustrating but not limitation to the embodiments. Based on the above description, other different forms of changes or variations can be made by those skilled in the art. Here, all the embodiments need not and can not be enumerated. The obvious changes or variations derived from the above description are still within the protection scope of the present application.

Claims

1. A type of iron-silicon magnetic powder, characterized in that, The iron-silicon magnetic powder is a layered iron-silicon magnetic powder; The iron-silicon magnetic powder includes a sheet-like iron-silicon core and an insulating coating layer covering the surface of the iron-silicon core. The iron-silicon magnetic powder reaches the iron-silicon core through the acid-permeable insulating coating layer, forming an acid passivation film at the interface between the iron-silicon core and the insulating coating layer.

2. The iron-silicon magnetic powder according to claim 1, characterized in that, The iron-silicon core comprises an iron-silicon alloy; The iron-silicon alloy comprises, by mass percentage: 93.2-96.2 wt% iron and 3.8-6.8 wt% silicon. And / or, the insulating coating material in the insulating coating layer is a nano-sized insulating coating material, and the average particle size of the nano-sized insulating coating material is 200-500nm; And / or, the insulating coating material in the insulating coating layer includes at least one of nano-mica powder, nano-silica, nano-alumina, and nano-kaolin. And / or, the acid includes at least one of phosphoric acid, chromic acid, and phytic acid.

3. A method for preparing the iron-silicon magnetic powder according to claim 1 or 2, characterized in that, Includes the following steps: 1) Take the molten iron-silicon alloy and atomize it to obtain alloy powder. Mix the alloy powder, surfactant and first solvent and ball mill it to obtain ball milling material; 2) Mix the ball milling material, insulating coating material and dispersant obtained in step 1), dry them, and then place the dried solid material in an acidic organic solvent for impregnation. After impregnation, the iron-silicon magnetic powder is obtained.

4. The method for preparing iron-silicon magnetic powder according to claim 3, characterized in that, The surfactant mentioned in step 1) is selected from at least one of oleic acid, lauric acid, and sodium secondary alkyl sulfonate; And / or, the first solvent is selected from acetone; And / or, the mass ratio of the alloy powder, surfactant, and first solvent is (3.5-7.0):(1-1.5):(7.5-12.5); And / or, the mass ratio of the grinding balls used in the ball mill to the mass of the alloy powder is (3.5-7):(1-1.5); And / or, the ball milling speed is 250-500 rpm, and the ball milling time is 4-5 h; And / or, the atomizing gas pressure of the gas atomization powder is 18-22 bar; And / or, after the gas atomization powdering step is completed, the process further includes a step of sieving the alloy powder after gas atomization powdering, wherein the alloy powder with a particle size of 200-500 mesh obtained by sieving is mixed with a surfactant and a first solvent and ball-milled.

5. The method for preparing iron-silicon magnetic powder according to claim 3 or 4, characterized in that, The mass ratio of the ball milling material to the insulating coating material mentioned in step 1) is 1:(0.001-0.012); And / or, the mass ratio of the ball milling material to the dispersant is 1:(1-4); And / or, the dispersant is selected from acetone; And / or, the mass ratio of acid in the acid-containing organic solvent to the mass ratio of ball milling material in the dried solid material is (0.004-0.008):1; And / or, the organic solvent is selected from acetone; And / or, the mass ratio of the acid to the organic solvent in the acid-containing organic solvent is 1:(2-4); And / or, the immersion time is 5-15 min.

6. A type of iron-silicon magnetic core, characterized in that, The iron-silicon magnetic core is prepared from the iron-silicon magnetic powder described in claim 1 or 2, or from the iron-silicon magnetic powder prepared by any one of the preparation methods described in claims 3-5.

7. A method for preparing an iron-silicon magnetic core, characterized in that, Includes the following steps: The iron-silicon magnetic powder prepared by the method described in claim 1 or 2 or any one of claims 3-5 is mixed with a lubricant, molded, and then heat-treated in an inert atmosphere to obtain the iron-silicon magnetic core.

8. The method for preparing an iron-silicon magnetic core according to claim 7, characterized in that, The mass ratio of the iron-silicon magnetic powder to the lubricant is 1000:(1-5); And / or, the lubricant is selected from zinc stearate; And / or, the molding pressure is 900-1200 MPa; And / or, the inert atmosphere includes at least one of nitrogen atmosphere and argon atmosphere; And / or, the heat treatment temperature is 700-760℃, and the heat treatment time is 20-40 min; And / or, the heating time of the heat treatment does not exceed 120 min.

9. The method for preparing an iron-silicon magnetic core according to claim 7 or 8, characterized in that, The molding process is preceded by ultrasonic vibration treatment. Optionally, the ultrasonic power of the ultrasonic vibration treatment is 50-100W, and the ultrasonic vibration treatment time is 30-180s; Optionally, the ultrasonic vibration treatment may also include a pre-compression treatment. Optionally, the pre-compression pressure is 48-52 MPa.

10. The application of the iron-silicon magnetic powder according to claim 1 or 2, or the iron-silicon magnetic powder prepared by the preparation method according to any one of claims 3-5, or the iron-silicon magnetic core according to claim 6, or the iron-silicon magnetic core prepared by the preparation method according to any one of claims 7-9, in inductive devices.